2001
DOI: 10.1063/1.1323252
|View full text |Cite
|
Sign up to set email alerts
|

Point-projection x-ray radiography using an X pinch as the radiation source

Abstract: Using an X pinch as a source of radiation for point-projection radiography, it is possible to project a high-resolution (1–10 μm) shadow image of dense plasma or test objects onto x-ray-sensitive film. The emission characteristics of X pinches composed of a wide variety of materials have been studied using several diagnostics. The pulse duration and shape of the x-ray bursts were measured in the 1.5–6 keV band using fast diamond PCDs and an x-ray streak camera with sweep speeds as fast as 10 ns for the full sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 5 publications
(1 reference statement)
0
34
0
1
Order By: Relevance
“…velopment of exotic properties: up to T e ∼ 1 keV and n e ∼ 10 22 cm −3 , in a highly localized hotspot (Zakharov et al 1982;Shelkovenko et al 2001aShelkovenko et al , 2001bShelkovenko et al , 2002. This has led to their application as an x-ray (1-10 keV) backlighter by Pikuz et al (1997) and Shelkovenko et al (2001b) for diagnosing dense plasmas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…velopment of exotic properties: up to T e ∼ 1 keV and n e ∼ 10 22 cm −3 , in a highly localized hotspot (Zakharov et al 1982;Shelkovenko et al 2001aShelkovenko et al , 2001bShelkovenko et al , 2002. This has led to their application as an x-ray (1-10 keV) backlighter by Pikuz et al (1997) and Shelkovenko et al (2001b) for diagnosing dense plasmas.…”
mentioning
confidence: 99%
“…This has led to their application as an x-ray (1-10 keV) backlighter by Pikuz et al (1997) and Shelkovenko et al (2001b) for diagnosing dense plasmas. Pikuz et al (2002) showed that these systems can be driven with currents as low as a few tens of kilo-amps, and are therefore a convenient and low-cost medium for the study of high energy density (>10 11 J/m 3 ) and radiation dominated plasmas.…”
mentioning
confidence: 99%
“…8,9 These hot spots are of great interest for their high energy density conditions and are used as a source for high energy radiography. 7,[10][11][12][13][14][15] Following the x-ray burst, plasma is rapidly evacuated from the central region, leaving a gap in the axial density profile which continually expands late in time. 7,13,16 Much of the research on x-pinches has been to characterize the implosion dynamics at the cross point, in order to more fully understand the x-ray generation mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies of X pinches and their x-ray backlighter applications have been performed previous to this work. [1][2][3] The present article focuses on the experimental and theoretical study of radiative properties of X pinches made from the alloys nichrome and conichrome. The description of the experiment is presented in Sec.…”
Section: Introductionmentioning
confidence: 99%